Pengaruh Quality of Friendship dan Subjective Well Being terhadap Hardiness Santri Pondok Pesantren Modern Al Amanah Al Gontory - Kholilah, Kholilah; Baidun, Akhmad (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2020)
This study aims to prove the influence of the quality of friendship (stimulating friendship, help, intimacy, reliable alliances, self-validation, and emotional security) and subjective well-being (cognitive and affective aspects) on the characteristics of santri in the Islamic Boarding School of Al Amanah Al Gontory Pesantren. This research uses quantitative with multiple regression analysis method. The winning sample is 240 santri. The instrument collects data using a scale compiled by the author based on hardiness theory by Kobasa (1982), friendship quality theory by Mendelson and Aboud (2012), and subjective wellness theory by Diener, Lucas, and Oishi (2002). The results showed that there were significant differences in the quality of friendship and subjective well-being of santri of the Islamic Boarding School of Al Amanah Al Gontory Pesantren.